THE RELATIONSHIP BETWEEN AGE, EDUCATION, AND KNOWLEDGE LEVEL ON THE NUTRITIONAL STATUS OF PREGNANT WOMEN AT THE JOHAN PAHLAWAN PUSKESMAS WEST ACEH REGENCY - Nurdanal Maulida; Safrida; M.Irfan Febriansyah; Suci Eka Putri (PT. Radja Intercontinental Publishing, 2024)
Background: According to the World Health Organization (WHO), chronic energy deficit is associated with 40% of maternal mortality in underdeveloped nations. An assessment of pregnant women's nutritional health may be done through several methods, including the Upper Arm Circumference (UAC) test. If the UAC measurement comes out less than 23.5 cm, it indicates that pregnant women's nutritional status is inadequate. Pregnant women's nutritional health might be positively or negatively impacted by their mothers' knowledge of meal selection. Babies born to mothers who do not get enough nourishment may be born with a host of issues. Objective: to learn how the nutritional status of pregnant women at the Johan Pahlawan Puskesmas is affected by factors including age, education, and knowledge level. Methods: This type of research is an analytic survey with a cross-sectional approach. Data collection techniques are quantitative research. This research was conducted on 48 samples and was carried out from June 26 to July 4, 2024, on pregnant women at the Johan Pahlawan Puskesmas. The measuring instruments used were questionnaires and UAC test. The data analysis method used Spearman's rank correlation coefficient for the statistical test. Research Results: there is a relationship between age, education, and knowledge level to the nutritional status of pregnant women at Puskesmas Johan Pahlawan with a P-value age 0.014 < α ( 0.05), education with P-value 0.047 < α (0,05), knowledge with P-value 0.003 < α ( 0.05), respectively. Conclusion: there is a relationship between knowledge, age, education, and nutritional status in pregnant women in the work area of the Johan Pahlawan Puskesmas, West Aceh. Suggestion: It is expected that health services will provide health promotion activities for pregnant women in the work area of the Puskesmas and need to monitor the nutritional status of pregnant women every month, and it is necessary to identify other variables related to the nutritional status of pregnant women.